Analisis dan Desain Pembelajaran Merdeka Belajar pada Mata Pelajaran PAI - Kuni Baridah Aini; Moh. Sutomo; Mashudi Mashudi (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
Education is the process of facilitating learning, or the acquisition of knowledge, skills, values, morals, beliefs, and habits. Through education, one can have an understanding of something that makes him a critical human being in thinking and acting. The measure of educational success is seen from the involvement and participation of teachers as educators, students as learners, learning materials provided, teaching methods and infrast ructure provided. The new Minister of Education and Culture of Indonesia, Nadiem Makarim, has since issued circular letter number 1 of 2020 regarding the policy of independent learning in determining student graduation, raising pros and cons from various groups,